Switchable, reagent-controlled diastereodivergent photocatalytic carbocyclisation of imine-derived α-amino radicals - Maitland, JAP; Leitch, JA; Yamazaki, K; Christensen, KE; Cassar, DJ; Hamlin, TA; Dixon, DJ (Wiley, 2021)
A reagent-controlled stereodivergent carbocyclisation of aryl aldimine-derived, photocatalytically-generated, α-amino radicals possessing adjacent conjugated alkenes, affording either bicyclic or tetracyclic products, is described. Under net reductive conditions using commercial Hantzsch ester, the α-amino radical species underwent a single stereoselective cyclisation to give trans-configured amino-indane structures in good yield, whereas using a substituted Hantzsch ester as a milder reductant afforded cis-fused tetracyclic tetrahydroquinoline frameworks, resulting from two consecutive radical cyclisations. Judicious choice of the reaction conditions allowed libraries of both single and dual cyclisation products to be synthesised with high selectivity, notable predictability, and good-to-excellent yields. Computational analysis employing DFT revealed the reaction pathway and mechanistic rationale behind this finely-balanced yet readily-controlled photocatalytic system.